Rigid Pavement Thickness Planning Using The Aashto 1993 Method On The Road Section Of Danau Rawah Village, Kapuas District, Central Kalimantan - Suwaji Suwaji; Rezky Anisari; Ria Adriyati (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The road section of Danau Rawah Village, Timah District, Kapuas Regency, has a length of 1 km with a road width of 3 meters. This section is a local road (rural collector) with 1 lane and 2 directions without a separator median, connecting different subdistricts. The condition of this road is that it is still unpaved and graveled. Therefore, there is a need to plan the appropriate road pavement thickness according to field conditions and in compliance with regulations. This research plans the rigid pavement thickness using the AASHTO 1993 method with a planned lifespan of 20 years. The calculated values include the concrete slab thickness, the thickness of the surface pavement, and soil improvement based on the subgrade's CBR data. The LHR data is obtained through direct surveys as the analytical material to obtain the planned traffic design values. The results obtained in the study of rigid pavement thickness planning using the AASHTO 1993 method for a planned lifespan of 20 years are as follows: the thickness of the concrete slab for the rigid pavement is 20 cm, the thickness of the upper pavement layer is 20 cm, and the process or improvement of the subgrade is 10 cm.